Theoretical fuel element modelling at CNEA - Harriague, Santiago; Savino, Eduardo José; Coroli, G.; Basombrío, Fernando Guillermo; Sánchez Sarmiento, G. (North-Holland Publishing Company, 1980)
Fil: Harriague, Santiago Comisión Nacional de Energía Atómica; Argentina